2023
DOI: 10.1098/rsos.230741
|View full text |Cite
|
Sign up to set email alerts
|

The prelude to industrial whaling: identifying the targets of ancient European whaling using zooarchaeology and collagen mass-peptide fingerprinting

Youri van den Hurk,
Fanny Sikström,
Luc Amkreutz
et al.

Abstract: Taxonomic identification of whale bones found during archaeological excavations is problematic due to their typically fragmented state. This difficulty limits understanding of both the past spatio-temporal distributions of whale populations and of possible early whaling activities. To overcome this challenge, we performed zooarchaeology by mass spectrometry on an unprecedented 719 archaeological and palaeontological specimens of probable whale bone from Atlantic European contexts, predominantly dating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…However, due to the limited availability of species-level identified whales from Bronze Age Netherlands, we included archaeological findings from other periods, as well as the modern distribution of the candidate species. The presence of Eubalaena glacialis is attested in the Netherlands from the mid-Holocene (Foote et al 2013) and at least the first millennium AD onwards (van den Hurk, Spindler, and McGrath 2022) and it has been tentatively suggested that this species might have been one of the most frequently exploited cetaceans along the European Atlantic coast (van den Hurk et al 2023). The two other candidate species, Eubalaena japonica (North Pacific right whale) and Eubalaena australis (southern right whale), are native to the North Pacific Ocean (Kenney 2009) and the southern hemisphere, respectively (Richards 2009) and can therefore be safely excluded as potential sources of sample 2199.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, due to the limited availability of species-level identified whales from Bronze Age Netherlands, we included archaeological findings from other periods, as well as the modern distribution of the candidate species. The presence of Eubalaena glacialis is attested in the Netherlands from the mid-Holocene (Foote et al 2013) and at least the first millennium AD onwards (van den Hurk, Spindler, and McGrath 2022) and it has been tentatively suggested that this species might have been one of the most frequently exploited cetaceans along the European Atlantic coast (van den Hurk et al 2023). The two other candidate species, Eubalaena japonica (North Pacific right whale) and Eubalaena australis (southern right whale), are native to the North Pacific Ocean (Kenney 2009) and the southern hemisphere, respectively (Richards 2009) and can therefore be safely excluded as potential sources of sample 2199.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sites indicate an overall marine focus of the culture, displayed by their diet and material culture (Brinkkemper, Drenth, and Zeiler 2011; van den Hurk et al 2023). The case for active whaling in 6th century Scandinavia is more robust.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations